Women Rights in the Arab Gulf States: Impact of 9/11 and Arab Uprisings - Azam, Muhammad (Pakistan Languages and Humanities Review, 2024)
The objective of this study is to examine the impact of the Arab uprisings and the events of 9/11 on women rights in the Gulf countries. In the aftermath of 9/11, how did the Arab Gulf states respond to global calls for democratic reforms? This is the key question explored in this study. The beginning of the twenty-first century saw the removal of various restrictions against women and the adoption of several reforms, both of which were met with positive reception on national and international levels. This qualitative study investigates the women-rights reforms introduced in the Gulf region following American after the 9/11 attacks. Similarly, the 2011 Arab uprisings alarmed the monarchs of the Gulf, leading them to adopt a carrot-and-stick approach. As a result, further reforms addressing women rights were introduced. Women in the Gulf states need to continue to push the boundaries for their rights and rightful liberties.